A survey of critical care pharmacists to patient ratios and practice characteristics in intensive care units. Issue 1 (1st August 2019) - Newsome, Andrea S.; Smith, Susan E.; Jones, Timothy W.; Taylor, Ashley; Van Berkel, Megan A.; Rabinovich, Marina
Abstract: Introduction: Pharmacists are widely recognized members of the critical care health care team. However, unlike other health care professions, critical care pharmacists do not have standardized pharmacist to patient ratios that establish maximal cost‐efficiency while maintaining optimal patient safety. Though many prior recommendations claim a ratio of 1:15 for safe pharmacy practice, recommendations have ranged as low as 1:8 to as high as 1:30. Objectives: To determine critical care pharmacists' perceptions of pharmacist to patient ratios within the intensive care unit (ICU) and qualitatively and quantitatively describe critical care pharmacist work environments. Methods: A cross‐sectional survey of pharmacists was conducted to identify current pharmacist to patient ratios and identify pharmacist perceptions of the safety of these ratios. Responses were presented using descriptive statistics. Multiple linear regression was conducted to determine factors associated with perceptions of workload and patient safety. Results: The response rate was 11% (n = 185). The majority of respondents reported participating in activities beyond patient care. The majority of pharmacists cared for more than 15 patients daily (n = 155, 84%), and 16% took care of 15 or fewer patients. About 30% of pharmacists did not feel the pharmacist to patient ratio optimized patient safety, and over half reported perceptions overwork. A majority of participants (n = 130, 76%) expressed a need for additional critical care pharmacists at their institutions. Higher pharmacist to patient ratios were associated with increased perception of unsafe patient care −.343 (−.507 to −.180, P  < .001). Conclusions: Heterogeneity exists among critical care pharmacy activities that may influence pharmacists' perceptions of workload and patient safety. Critical care pharmacists report that their institutions should have more critical care pharmacists. Pharmacists' perceptions of workload vary based on differences in their activities outside of patient care.